P2X7R Mediates the Synergistic Effect of ATP and MSU Crystals to Induce Acute Gouty Arthritis. (12th January 2023) - Li, Xiaoling; Wan, An; Liu, Yiming; Li, Manyun; Zhu, Ziwen; Luo, Chengyu; Tao, Jinhui
Abstract : Activation of the nod-like receptor protein 3 (NLRP3) inflammasome by monosodium urate (MSU) crystals has been identified as the molecular basis for the acute inflammatory response in gouty arthritis. However, MSU crystals alone are not sufficient to induce acute gouty arthritis (AGA). Adenosine triphosphate (ATP) is an endogenous signaling molecule involved in the NLRP3 inflammasome activation. We aimed to explore the role of ATP in MSU crystal-induced AGA development. In peripheral blood mononuclear cell-derived macrophages obtained from gout patients, we observed a synergistic effect of ATP on MSU crystal-induced IL-1 β release. Furthermore, in a rat model of spontaneous gout, we demonstrated that a synergistic effect of ATP and MSU crystals, but not MSU crystals alone, is essential for triggering AGA. Mechanistically, this synergistic effect is achieved through the purinergic receptor P2X7 (P2X7R). Blockade of P2X7R prevented AGA induction in rats after local injection of MSU crystals, and carrying the mutant hP2X7R gene contributed to the inhibition of NLRP3 inflammasome activation induced by costimulation of MSU crystals and ATP in vitro . Taken together, these results support the synergistic effect of ATP on MSU crystal-induced NLRP3 inflammasome activation facilitating inflammatory episodes in AGA. In this process, P2X7R plays a key regulatory role, suggesting targeting P2X7R to be an attractive therapeutic strategy for the treatment of AGA.